(untitled) (Journal of the College of Education for Women, 2019)
The Holy Koran is the highest text in the eloquence, It is one of theimportant sources of the linguistic syntactic and eloquent study; it impactsupon these sciences Avery intense impact through advancing its verses as anargument in the confirmation of the significance of the termThe holy Koran was and still the fountain of the linguistic studies, asthey tend towards it since the second century of the hegira. So this research isa study of the expressive terms concerning the rain in the holly Koran, alinguistic study; it aims to study the term concerning its linguistic andconjugate significance and its expression concerning the rain through realityand metaphor.